INOVASI DAN TANTANGAN PEMBELAJARAN FISIKA DI SMA NEGERI 2 TONDANO PADA ERA PERUBAHAN KURIKULUM - Fitrianingrum, Aufa Maulida; Silangen, Patricia Mardiana; Loding, Intan Eka Audrey; Makarawung, Putri S.; Muhammad, Yufita Dwi (Charm Sains: Jurnal Pendidikan Fisika, 2025)
This study aims to analyze the implementation of the curriculum and its impact on physics learning at SMA Negeri 2 Tondano. The research method used is a qualitative approach consisting of several stages: preparation, data collection, data analysis, and conclusion drawing. The data collection techniques employed include observation and interviews conducted at SMA Negeri 2 Tondano. The research subject is the physics teacher at the school. The results of this study show that SMA Negeri 2 Tondano has implemented a curriculum aligned with the national curriculum policy. Since the 2023/2024 academic year, all classes have adopted the Merdeka Curriculum, while previous cohorts were still using the 2013 Curriculum (K-13). In physics learning, teachers strive to integrate project-based approaches and simple experiments to enhance students’ conceptual understanding. In addition, innovations such as the use of PhET simulations and interactive digital media have begun to be implemented to help students visualize abstract physical phenomena. Both teachers and students perceive that the curriculum development has brought positive benefits to the learning process. However, teachers also face challenges such as limited laboratory equipment, varying levels of students’ technological proficiency, and the need for continuous professional development to adapt to the dynamic changes in the curriculum.